Perovskite solar cell based on variable valence metal oxide layer and preparation method thereof

By introducing a variable valence metal oxide layer into perovskite solar cells, and using redox reaction to promote electron and hole separation, the problems of large-area preparation and long-term stability of perovskite solar cells are solved, and efficient battery performance and reduction are achieved It is suitable for industrial applications.

CN119136570AActive Publication Date: 2024-12-13SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310688606.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

Perovskite solar cells have challenges in large-area preparation and long-term stability, and the existing methods are costly and are not suitable for industrial applications.

Method used

The variable valence metal oxide layer is introduced into the perovskite solar cell, which promotes the separation of electrons and holes through redox reactions. The variable valence metal oxide nanoparticle layer with a porous structure is adopted, combining cerium oxide, vanadium oxide, manganese oxide, and cobalt oxide. The material is such as the variable valence metal oxide layer between the back electrode and the mesoporous insulating layer, and the thickness thereof is adjusted to improve separation efficiency.

Benefits of technology

It improves the electron and hole separation efficiency of perovskite solar cells, improves battery efficiency and stability, reduces preparation costs, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136570A_ABST
    Figure CN119136570A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite solar cell based on a variable valence metal oxide layer and a preparation method thereof. The perovskite solar cell comprises a variable valence metal oxide layer formed between a back electrode and a mesoporous insulating layer; the components of the variable valence metal oxide layer comprise at least one of CeOx, VOy, MnOz, CoOa and MoOb; wherein 1 < = x < = 2, 1 < = y < = 2.5, 0.5 < = z < = 3.5, 1 < = a < = 1.5, and 0.5 < = b < = 3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a perovskite solar cell based on the redox reaction characteristics of a variable-valence metal oxide and a preparation method thereof, belonging to the field of perovskite solar cells. Background Art

[0002] Energy is an important driving force for economic and social development. my country's energy industry has developed rapidly and has become the world's largest energy producer and consumer, which has strongly supported economic and social development. However, my country's energy structure has long been dominated by coal, with a high degree of external dependence on oil and gas, and the need for clean and low-carbon energy transformation is urgent. Solar energy has the advantages of being clean, pollution-free and having huge reserves. How to efficiently use solar energy has become an important way to achieve low-carbon energy.

[0003] Perovskite solar cells stand out among a number of new solar cells due to their high photoelectric conversion efficiency, low cost, and easy manufacturing. At present, the main problems facing the industrialization of perovskite solar cells are large-area preparation and long-term stability. Fully printed carbon-based perovskite solar cells can solve these two major problems and have great industrialization potential.

[0004] It is now generally recognized that the basic working process of perovskite solar cells is divided into three stages, of which the first stage is to absorb the energy of photons and generate excited carriers; the second stage is the separation of carriers into free electrons and holes; the third stage is the transfer of free electrons and holes to the hole blocking layer and hole transport layer respectively. Therefore, from the perspective of energy band analysis, it is required that the energy barrier when electrons are injected into the hole transport layer should be high, so as to play a role in blocking electrons. Similarly, it is required that the potential barrier when holes are injected into the electron transport layer should be high. The energy level gradient and built-in electric field formed between the materials inside the device ensure that electrons and holes enter the external circuit along their respective transmission paths.

[0005] In contrast, Patent Document 1 (Chinese Patent Publication No. CN111864077A) discloses a method for reducing the degradation and attenuation of perovskite solar cells by introducing a redox couple into the perovskite absorption layer. Although the above method provides a method for reducing the degradation and attenuation of the perovskite absorption layer by utilizing redox reactions, its essence is still to passivate the defects of the perovskite light absorption layer material, and its preparation cost is relatively high, which is not suitable for industrial application. Summary of the invention

[0006] Based on the goal of promoting the industrialization of perovskite solar cells, the present invention provides a valence-variable metal oxide layer and a preparation method thereof and an application in perovskite solar cells.

[0007] In one aspect, the present invention provides a perovskite solar cell, comprising: a variable valence metal oxide layer formed between a back electrode and a mesoporous insulating layer; the variable valence metal oxide layer comprises CeO x , VO y 、MnO z 、CoO a 、MoO b At least one of the following; wherein 1≤x≤2, 1≤y≤2.5, 0.5≤z≤3.5, 1≤a≤1.5, 0.5≤b≤3.

[0008] Preferably, the variable valence metal oxide layer promotes the separation of electrons and holes through redox reaction. For example, since tetravalent cerium and trivalent cerium in cerium oxide are more easily converted, the energy required for valence state change is lower, which is more conducive to the separation of electrons and holes in perovskite.

[0009] Preferably, the variable-valence metal oxide layer is a porous structure layer composed of variable-valence metal oxide nanoparticles; the particle size of the variable-valence metal oxide nanoparticles is 5nm to 100nm, and the porous pore size of the variable-valence metal oxide layer is 2nm to 300nm.

[0010] Preferably, the thickness of the variable valence metal oxide layer is 0.05 μm to 20 μm, preferably 0.05 μm to 10 μm. The variable valence metal oxide layer serves as a redox reaction layer to regulate the CeO x , VO y 、MnO z 、CoO a 、MoO b The thickness of the variable-valence metal oxide layer affects the separation efficiency of electrons and holes in perovskite solar cells.

[0011] Preferably, the perovskite solar cell comprises: Transparent conductive substrate; A dense layer, a mesoporous electron transport layer, a mesoporous insulating layer, a variable valence metal oxide layer and a back electrode layer are sequentially formed on a transparent conductive substrate; And perovskite light-absorbing materials distributed in the mesoporous electron transport layer, the mesoporous insulating layer and the variable-valence metal oxide layer.

[0012] Preferably, the transparent conductive substrate is a FTO transparent conductive layer or an ITO transparent conductive layer.

[0013] Preferably, the dense layer is selected from at least one of titanium oxide and its dopants, zinc oxide and its dopants, tin oxide and its dopants, and the thickness of the dense layer is 10 nm to 100 nm.

[0014] Preferably, the component of the mesoporous electron transport layer is selected from at least one of titanium dioxide and its dopants, tin oxide and its dopants, zinc oxide and its dopants, and the thickness of the mesoporous electron transport layer is 0.2 μm to 5 μm.

[0015] Preferably, the mesoporous insulating layer is at least one of aluminum oxide and zirconium oxide, and the thickness of the mesoporous insulating layer is 0.5 μm to 10 μm.

[0016] Preferably, the back electrode layer is a porous carbon electrode, and the constituent material of the porous carbon electrode is at least one of flaky graphite, carbon black, carbon fiber, carbon nanotubes and dopants thereof.

[0017] Preferably, the chemical formula of the perovskite light absorbing material is ABX3, wherein A is a monovalent cation, B is a divalent metal ion, and X is a monovalent halogen or pseudohalogen ion.

[0018] Furthermore, preferably, the chemical formula of the perovskite light absorbing material is ABX3; wherein A is a cation of an organic amine or an alkali metal ion, preferably CH3NH3 + 、CH5N2 + , Cs + At least one of; B is Pb 2+ Sn 2+ , Fe 2+ 、Co 2+ At least one of; X is Cl - Br - ,I - 、SCN - At least one of; More preferably, the perovskite light absorbing material is (5-AVA) c MA 1- c PbI3, 0≤c≤1.

[0019] On the other hand, the present invention provides a method for preparing a perovskite solar cell, wherein the variable-valence metal oxide layer is prepared by coating a slurry containing variable-valence metal oxide nanoparticles on the surface of a mesoporous insulating layer, followed by drying and sintering to obtain the variable-valence metal oxide layer.

[0020] Preferably, the mass fraction of the slurry containing variable-valence metal oxide nanoparticles is 2% to 50%; The drying temperature is 30 to 150° C. and the drying time is 5 to 300 minutes; The sintering temperature is 300-600° C. and the sintering time is 20-90 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1A schematic diagram of the structure of a perovskite solar cell according to an embodiment is shown; Figure 2 The JV curves of the perovskite solar cells obtained in Example 1 and Comparative Examples 1 and 2 are shown. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0023] In the present invention, a perovskite solar cell that improves efficiency based on redox characteristics, in combination with the attached drawings, includes a transparent conductive substrate 1, and a dense layer 2, a mesoporous electron transport layer 3, a mesoporous insulating layer 4, a variable valence metal oxide layer 5 and a back electrode layer 6 formed in sequence on the transparent conductive substrate; wherein the perovskite light absorbing material is filled in the mesoporous electron transport layer 3, the mesoporous insulating layer 4, and the variable valence metal oxide layer 5.

[0024] In an optional embodiment, the chemical formula of the perovskite light absorbing material is ABX3, wherein A is a cation of an organic amine or an alkali metal ion, preferably CH3NH3 + 、CH5N2 + , Cs + At least one of the following, B is Pb 2+ Sn 2+ , Fe 2+ 、Co 2+ At least one of, X is Cl - Br - ,I - 、SCN - At least one of the following is evenly distributed in each functional layer. Preferably, the perovskite material is (5-AVA) c MA 1-c PbI3.

[0025] In the embodiment of the present invention, the use of variable valence metal oxide as the reaction layer can achieve a more effective cycle reaction, thereby improving the battery efficiency. The following is an exemplary description of the preparation method of the perovskite solar cell based on the redox reaction of the variable valence metal oxide.

[0026] A dense layer, a mesoporous electron transport layer, and a mesoporous insulating layer are sequentially prepared on a transparent conductive substrate, wherein the transparent conductive substrate is a FTO transparent conductive layer or an ITO transparent conductive layer.

[0027] In an optional embodiment, the dense layer may be at least one of titanium oxide and its dopants, zinc oxide and its dopants, tin oxide and its dopants. Methods for preparing the dense layer include: screen printing, spin coating, spray coating, blade coating, and the like.

[0028] In an optional embodiment, the mesoporous electron transport layer is a TiO2 mesoporous layer. Methods for preparing the mesoporous electron transport layer include: screen printing, spin coating, spray coating, blade coating, etc.

[0029] In an optional embodiment, the mesoporous insulating layer is a mesoporous ZrO2 or Al2O3 insulating layer. Methods for preparing the mesoporous insulating layer include: screen printing, spin coating, spray coating, blade coating, etc.

[0030] A variable valence metal oxide layer with porous pores is prepared on the mesoporous insulating layer by screen printing and sintering. The dry film thickness of the obtained variable valence metal oxide layer is 0.05 μm to 20 μm. The solid content of the variable valence metal oxide slurry used is 2 wt% to 50 wt%.

[0031] The reaction layer slurry is prepared by screen printing, and the mesh size of the screen used for printing the reaction layer slurry is 200-600 meshes.

[0032] The sintering includes: sintering in a muffle furnace at 300-600° C. for 20-90 minutes. Before sintering, the product may be dried in air and then transferred to the muffle furnace. The drying temperature may be 30-150° C. and the drying time may be 5-300 minutes.

[0033] A back electrode (eg, a porous carbon electrode) is prepared on the variable valence metal oxide film layer. Preferably, the porous carbon electrode has a thickness of 5 μm to 100 μm. Methods for preparing the porous carbon electrode include: screen printing, scraping, spraying, and the like.

[0034] A certain amount of perovskite precursor solution is dripped on the top of the back electrode (e.g., porous carbon electrode), left to stand, and then heated under a certain humidity. Preferably, the perovskite is (5-AVA) c MA 1-c PbI3, 0≤c≤1, the humidity is between 30%-80% RH.

[0035] In the present invention, cerium oxide is placed in the hole transport layer position, and an unexpected effect is obtained. The perovskite solar cell wherein improves its efficiency and stability through the redox characteristics of the variable valence metal oxide layer. The variable valence metal oxides are such as cerium oxide, vanadium oxide, manganese oxide, cobalt oxide, molybdenum oxide, etc. The difference from the conventional nip-type or pin-type perovskite solar cell is that its essence is to promote the separation of electrons and holes through a mild redox reaction layer, thereby continuously generating photocurrent.

[0036] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0037] Embodiment 1: 1) Etching the FTO glass substrate with a laser to form the desired pattern; 2) The FTO glass was cleaned with acetone, alkaline detergent, deionized water, and acetone ultrasonically for about 20 minutes, then dried, and treated with UV-ozone for about 15 minutes; 3) preparing a dense layer 2 on the FTO glass 1. Taking the titanium dioxide dense layer as an example, the film is formed by spin coating or printing, and sintered in a muffle furnace at 300-600° C. (e.g. 500° C.) for 20-90 minutes (e.g. 30 minutes); 4) A mesoporous layer 3 is formed on the dense titanium dioxide layer 2. Taking mesoporous titanium dioxide as an example, the following steps are included: a: Prepare nano-titanium dioxide into a titanium dioxide slurry with a mass fraction of 5%-20%, and the main components include anhydrous ethanol, ethyl cellulose, pine alcohol, and titanium dioxide. b: Print mesoporous titanium dioxide on the dense titanium dioxide layer that has been treated with UV-ozone for 15 minutes. c: Place the glass sheet brushed with mesoporous titanium dioxide in a muffle furnace at 300-600°C (for example, 500°C) and sinter for 20-90 minutes (for example, 30 minutes); 5) An insulating layer 4 is formed on the mesoporous titanium dioxide layer 3. Taking zirconium dioxide as an example, the following steps are included: a: Prepare nano zirconium dioxide into a zirconium dioxide slurry with a mass fraction of 5%-20%, and the main components include anhydrous ethanol, ethyl cellulose, pine alcohol, and zirconium dioxide. b: Print insulating zirconium dioxide on the mesoporous titanium dioxide layer that has been treated with UV-ozone for 15 minutes. c: Place the glass sheet brushed with insulating zirconium dioxide in a muffle furnace at 300-600°C (for example, 500°C) and sinter for 20-90 minutes (for example, 30 minutes); 6) Form a variable valence metal oxide reaction layer 5 on the insulating zirconium dioxide 4. Taking cerium oxide as an example, the following steps are included: a: Prepare nano cerium oxide into a cerium oxide slurry with a mass fraction of 2%-50%, and the main components include anhydrous ethanol, ethyl cellulose, pinene alcohol, and cerium oxide. b: Print the variable valence metal oxide reaction layer on the zirconium dioxide insulating layer that has been treated with UV-ozone for 15 minutes. c: Place the glass sheet brushed with the variable valence metal oxide in a muffle furnace at 300-600°C (for example, 500°C) and sinter for 20-90 minutes (for example, 30 minutes); 7) Forming a back electrode 6 on the variable valence metal oxide reaction layer 5. Taking the porous carbon electrode as an example, the following steps are included: a: Printing a carbon electrode on the variable valence metal oxide reaction layer after UV-ozone treatment for 15 minutes. b: Placing the glass sheet with the brushed carbon electrode in a muffle furnace at 200-500°C (e.g. 430°C) for sintering for 20-90 minutes (e.g. 30 minutes); 8) Take 0.5761g PbI2, 0.1953g MAI and 0.0152g 5-AVAI and dissolve them in 1mL of a mixed solvent of ethanol and γ-butyrolactone (Vethanol:Vγ-butyrolactone=1:4). After stirring at room temperature for 6 hours, take 5μL of the perovskite solution and drop it on the back electrode 6. After heating at 50°C for 1 hour, a perovskite solar cell was obtained.

[0038] Comparative Example 1: In this comparative example 1, no variable valence metal oxide reaction layer is prepared, and the preparation method steps of other layers are the same as those in Example 1, including the following steps: 1) Laser etching, same as in Example 1; 2) Cleaning the FTO glass, as in Example 1; 3) Preparing a dense layer on the FTO glass, as in Example 1; 4) forming a mesoporous titanium dioxide layer on the titanium dioxide dense layer, as in Example 1; 5) forming a mesoporous insulating layer on the mesoporous titanium dioxide layer, as in Example 1; 6) forming a back electrode on the insulating layer of zirconium dioxide, as in Example 1; 7) Prepare a perovskite precursor solution and prepare a perovskite solar cell, as in Example 1.

[0039] Comparative Example 2: 1) Laser etching, same as in Example 1; 2) Cleaning the FTO glass, as in Example 1; 3) Preparing a dense layer on the FTO glass, as in Example 1; 4) forming a mesoporous layer on the titanium dioxide dense layer, as in Example 1; 5) forming an insulating layer on the mesoporous titanium dioxide layer, as in Example 1; 6) Forming a p-type nickel oxide layer on the insulating layer of zirconium dioxide, comprising the following steps: a: preparing nano nickel oxide into a nickel oxide slurry with a mass fraction of 2%-50%, the components of which mainly include anhydrous ethanol, ethyl cellulose, pine alcohol, and nickel oxide. b: printing a variable valence metal oxide reaction layer on the zirconium dioxide insulating layer after UV-ozone treatment for 15 minutes. c: placing a glass sheet brushed with a wet nickel oxide film in a muffle furnace at 300-600°C (e.g. 500°C) and sintering for 20-90 minutes (e.g. 30 minutes); 7) forming a back electrode on the variable-valence metal oxide reaction layer, as in Example 1; 8) Preparing a perovskite precursor solution and preparing a perovskite solar cell, the same as in Example 1.

[0040] Table 1 shows the performance of the perovskite solar cells prepared in Example 1 of the present invention and Comparative Examples 1-2: Cell Voc[V] <![CDATA[Jsc[mA / cm 2 ]]]> FF[%] Eff[%] Rs[ohm] Rsh[ohm] Wpm[mW] Comparative Example 1 0.879 24.26 57.37 12.24 123.71 4643.7 0.856 Comparative Example 2 0.922 24.93 63.1 14.52 98.93 9083.2 1.016 Example 1 0.975 25.37 65.93 16.31 78.12 12909.2 1.142 .

[0041] Figure 2 The JV curves of the perovskite solar cells prepared in Example 1 and Comparative Examples 1-2 are shown. From the figure, it can be seen that the V OC , FF, J SC and PCE are higher than those of the comparative example.

[0042] The above specific implementations further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above is only a specific implementation of the present invention and is not limited to the protection scope of the present invention. Without departing from the purpose of the basic characteristics of the present invention, the present invention can be embodied in various forms. Therefore, the implementation forms in the present invention are used for illustration rather than limitation. Since the scope of the present invention is limited by the claims rather than the specification, and all changes within the scope defined by the claims or within the equivalent scope of the scope defined by the claims should be understood to be included in the claims. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A perovskite solar cell, characterized in that: include: A variable valence metal oxide layer is formed between the back electrode and the mesoporous insulating layer; the variable valence metal oxide layer comprises CeO x , VO y 、MnO z 、CoO a 、MoO b At least one of the following; wherein 1≤x≤2, 1≤y≤2.5, 0.5≤z≤3.5, 1≤a≤1.5, 0.5≤b≤3.

2. The perovskite solar cell according to claim 1, characterized in that: The valence-varied metal oxide layer promotes separation of electrons and holes through redox reaction.

3. The perovskite solar cell according to claim 1, characterized in that: The variable-valence metal oxide layer is a porous structure layer composed of variable-valence metal oxide nanoparticles; the particle size of the variable-valence metal oxide nanoparticles is 5nm-100nm, and the porous pore size of the variable-valence metal oxide layer is 2nm-300nm.

4. The perovskite solar cell according to any one of claims 1 to 3, characterized in that: The thickness of the variable-valence metal oxide layer is 0.05 μm to 20 μm.

5. The perovskite solar cell according to any one of claims 1 to 4, characterized in that: include: Transparent conductive substrate; A dense layer, a mesoporous electron transport layer, a mesoporous insulating layer, a variable valence metal oxide layer and a back electrode layer are sequentially formed on a transparent conductive substrate; And perovskite light-absorbing materials distributed in the mesoporous electron transport layer, the mesoporous insulating layer and the variable-valence metal oxide layer.

6. The perovskite solar cell according to claim 5, characterized in that: The transparent conductive substrate is a FTO transparent conductive layer or an ITO transparent conductive layer; The dense layer is selected from at least one of titanium oxide and its dopants, zinc oxide and its dopants, tin oxide and its dopants, and the thickness of the dense layer is 10nm to 100nm. The component of the mesoporous electron transport layer is selected from at least one of titanium dioxide and its dopants, tin oxide and its dopants, zinc oxide and its dopants or binary composite oxides thereof, and the thickness of the mesoporous electron transport layer is 0.2 μm to 5 μm.

7. The perovskite solar cell according to claim 5, characterized in that: The mesoporous insulating layer is at least one of aluminum oxide and zirconium oxide, and the thickness of the mesoporous insulating layer is 0.5 μm to 10 μm; The back electrode layer is a porous carbon electrode, and the constituent material of the porous carbon electrode is at least one of flaky graphite, carbon black, carbon fiber, carbon nanotubes and dopants thereof; The chemical formula of the perovskite light absorbing material is ABX3, wherein A is a monovalent cation, B is a divalent metal ion, and X is a monovalent halogen or pseudohalogen ion.

8. The perovskite solar cell according to claim 7, characterized in that: The chemical formula of the perovskite light absorbing material is ABX3; wherein A is a cation of an organic amine or an alkali metal ion, preferably CH3NH3 + 、CH5N2 + , Cs + At least one of; B is Pb 2+ Sn 2+ , Fe 2+ 、Co 2+ At least one of; X is Cl - Br - ,I - 、SCN - At least one of; More preferably, the perovskite light absorbing material is (5-AVA) c MA 1-c PbI3, 0≤c≤1.

9. A method for preparing a perovskite solar cell as claimed in claim 1, characterized in that: The variable valence metal oxide layer is prepared by coating a slurry containing variable valence metal oxide nanoparticles on the surface of the mesoporous insulating layer, followed by drying and sintering to obtain the variable valence metal oxide layer.

10. The preparation method according to claim 9, characterized in that: The mass fraction of the slurry containing variable-valence metal oxide nanoparticles is 2% to 50%; The drying temperature is 30 to 150° C. and the drying time is 5 to 300 minutes; The sintering temperature is 300-600° C. and the sintering time is 20-90 minutes.

Citation Information

Patent Citations

  • Semi-conductor perovskite solar cell and preparing method thereof

    CN104091889A

  • Preparation method of silk-screen printing carbon paste and high-current-conductivity carbon electrode

    CN110504369A

  • Perovskite solar cell

    WO2017006839A1